Analisis penerapan sistem pengendalian manajemen dengan four levers of control (belief and diagnostic control system) pada PT Bank Negara Indonesia (persero) Tbk Cabang Tomohon - Ludong, Jurgen Gabriel Erick; Pangerapan, Sonny; Latjandu, Lady Diana (Manajemen Bisnis dan Keuangan Korporat, 2024)
Management control is one of the systems that can assist top-level management in efforts to achieve goals and control all business activities within an organization. There are several systems commonly used by companies in managing their operations, one of which is the Four Levers of Control. This research discusses how the management control system in Bank Negara Indonesia, Tomohon branch, is evaluated using the Four Levers of Control model, focusing on the Belief and Diagnostic Control System. The method used in this research is qualitative descriptive method, employing data collection methods such as interviews, observations, documentation, and literature review. Through this research, it was found that the Four Levers of Control, particularly focusing on the Belief and Diagnostic Control System, can have a positive influence on improving the performance of Bank BNI Tomohon branch.